Monitoring the readiness of sports teams in competitive sports among students - Rodin, A.V.; Ryzhkin, N.V.; Nemtseva, E.V.; Korobov, I.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to justify the content of integrative control of the preparedness of student teams in various game sports. Methods and structure of the study. During the 2024-2025 academic year, individual tactical actions and psychophysiological indicators of student teams from Smolensk State University of Sports and Don State Technical University were tested in basketball and volleyball, and indicators of compliance with control standards were determined as a result of integrative control of athletes' preparedness. Results and conclusions. The use of integrated monitoring of individual tactical actions and psychophysiological indicators of basketball and volleyball players allows for the collection, analysis, and interpretation of information, which forms the basis for effective management of training and competitive activities.